INVESTIGATION OF THE OPERATING CONDITIONS BY CUTTING OF POPLAR AND PINE LOGS THROUGH WIDE BAND SAW BLADES WITH PART-SET AND SWAGE-SET TEETH (Innovation in Woodworking Industry and Engineering design, 2026)
The paper presents some experimental results concerning cutting process of poplar and pine logs through wide band saw blades with part-set and swage-set teeth. The researches were carried out in a production process of company „Fagus Ltd“, town Pernik. The influence of the feed speed and height of cutting on the productivity of the process and energy consumption were analyzed. The results are suitable to have a better knowledge and work out of the production and operating indexes and its optimization by using of wide band saw blades.